Annual Variations in the Near-Earth Solar Wind - Owens Mathew J.; Lockwood Mike; Barnard Luke A.; Yardley Stephanie L.; Hietala Heli; LaMoury Adrian T.; Vuorinen Laura (Springer Dordrecht, 2025)
Earth’s orbit and rotation produces systematic variations in geomagnetic activity, most notably via the changing orientation of the dayside magnetospheric magnetic field with respect to the heliospheric magnetic field (HMF). Aside from these geometric effects, it is generally assumed that the solar wind in near-Earth is uniformly sampled. But systematic changes in the intrinsic solar wind conditions in near-Earth space could arise due to the annual variations in Earth heliocentric distance and heliographic latitude. In this study, we use 24 years of Advanced Composition Explorer data to investigate the annual variations in the scalar properties of the solar wind, namely the solar wind proton density, the radial solar wind speed and the HMF intensity. All parameters do show some degree of systematic annual variation, with amplitudes of around 10 to 20%. For HMF intensity, the variation is in phase with the Earth’s heliocentric distance variation, and scaling observations for distance largely explains the observed variation. For proton density and solar wind speed, however, the phase of the annual variation is inconsistent with Earth’s heliocentric distance. Instead, we attribute the variations in speed and density to Earth’s heliographic latitude variation and systematic sampling of higher speed solar wind at higher latitudes. Indeed, these annual variations are most strongly ordered at solar minimum. Conversely, combining scalar solar wind parameters to produce estimates of dynamic pressure and potential power input to the magnetosphere results in solar maximum exhibiting a greater annual variation, with an amplitude of around 40%. This suggests Earth’s position in the heliosphere makes a significant contribution to annual variations in space weather, in addition to the already well-studied geometric effects.